The Effects of Attractive Employees, Uniform & Other Customers on Image - Chan, Mun Wei (2010)
Our world is built around images which we have created with what we perceived as true. There will always be a label for everything in our lives; it is as such that it was our innate abilities to label and associate a certain images to a person, environment, organization, universe and everything which cross our paths. Consequently, our everyday behaviours and reactions were based and resulted by this images which we believe as true and not what is true (Boulding cited in Lindquist ,1974). These illustrate the importance of image to an organization since it is what customers used to define an organization. Hence, businesses and organizations shall strive to create, project and sustain their best image to their customers. Atmospheric design of a store has become the harbinger for image improvement especially for organizations which rely on their retail premises to deliver services to clientele. The personnel within the servicescape are communicators of the stores brand image both verbally as well as from just being in their uniforms and their demeanour. On the other hand, consumers are also part of the human factors in atmospheric design. The key objectives of this dissertation were to study how physical attractiveness and dress of contact personnel could affect the image of consumer banking industry in Malaysia. Moreover, effects which were caused by other customers such as crowding on image were examined. The focal point and scope of this study were gathered from external rather than internal customers. Quantitative methods were used in this research. 115 of questionnaires were given out to consumer residing in Klang Valley which has a bank account. A combination of pictures and scales were developed to operationalize and simulate real life situation in the questionnaires. Findings indicate that attractive service personnel help to improve store image and were perceived as reliable, professional, friendly, has integrity, helpful, knowledgeable, approachable, and efficient. Whereas relatively less attractive service personnel project negative image and were associated with negative traits and characteristics. Customers preferred and perceived positively service personnel wearing uniform compared to non-wearing uniform service personnel. Retail crowding in a bank projects negative image and deter patronage. Other customers‟ appearances do affect the image perception of customers and good appearances were preferred over sloppy appearances. Organization shall improve and adapt their human resources strategies to recruit new attractive service personnel while sending their existing employee to grooming and gym classes. Processes and procedures shall be improvised to best reduce retail crowding and help customers to fasten and eased their transactions. For example, placing some touch screen kiosks in the banking hall for customers to seek information on what documents required and which counter to go to. Guidelines on customers‟ appearance should be drawn to better improve store images. This can be first done and applied in selected signature branches especially those which served high net worth clienteles to gauge the responses before a full-fledge implementation.